Evaluation of Energy Saving Potential for Small and Medium Enterprises (SMEs) in Thailand - Wongkot Wongsapai (2018)
© 2017 The Authors. Published by Elsevier Ltd. Thailand focused on the energy conservation in designated factories and commercial buildings for more than 25 years, by the promulgation of the Energy Conservation Promotion Act, B.E.1992. However, there are many enterprises (i.e. factories and commercial buildings) which are not in the regulation's target but consume high amount of energy. This study focuses on the potential energy saving from the so called SMEs (in energy pattern) in Thailand. By using on-site energy consumption and production survey to the 860 SMEs covering eight industry and six commercial building sub-sectors over the country and energy savings by using ODEX estimation, we found that the estimated energy conservation potential in factories and commercial buildings are 881.43 GJ and 442.94 GJ, respectively. Food and beverage, especially in food canning has highest energy reduction potential in industry while hotel and hospital has highest potential saving in commercial building. The obstacles of the energy efficiency improvement in SMEs are also discussed.